2010
DOI: 10.1175/2009jamc2146.1
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Relationship between Soil Moisture and the Low-Level Jet and Its Role on the Prestorm Environment in the Southern Great Plains

Abstract: Changes in low-level moisture alter the convective parameters [e.g., convective available potential energy (CAPE), lifted index (LI), and convective inhibition (CIN)] as a result of alterations in the latent and sensible heat energy exchange. Two sources for low-level moisture exist in the southern Great Plains: 1) moisture advection by the low-level jet (LLJ) from the Gulf of Mexico and 2) evaporation and transpiration from the soils and vegetation in the region. The primary focus of this study is to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…9b, the increased soil moisture in the central United States enhances the west-east soil moisture gradient along the slope of the Rocky Mountains. By prescribing an increased zonal soil moisture gradient in a numerical model, Fast and McCorcle (1990) showed that the GPLLJ tends to intensify as a result of an increased zonal pressure gradient force (Fast andMcCorcle 1990, 1991;Pielke 2001;Frye and Mote 2010).…”
Section: Mechanisms: Dual Effects Of Soil Moisturementioning
confidence: 99%
“…9b, the increased soil moisture in the central United States enhances the west-east soil moisture gradient along the slope of the Rocky Mountains. By prescribing an increased zonal soil moisture gradient in a numerical model, Fast and McCorcle (1990) showed that the GPLLJ tends to intensify as a result of an increased zonal pressure gradient force (Fast andMcCorcle 1990, 1991;Pielke 2001;Frye and Mote 2010).…”
Section: Mechanisms: Dual Effects Of Soil Moisturementioning
confidence: 99%
“…Global climate models have identified the US Southern Great Plains as a "hot spot" of land-atmosphere interactions wherein the probability of precipitation responds strongly to land surface conditions (Koster et al, 2004). Studies employing soil moisture observations show less consistent results, with some suggesting a wet soil advantage regime in the region (Frye and Mote, 2010b;Ford et al, 2015), and others providing evidence of a dry soil advantage regime (Santanello et al, 2013;Guillod et al, 2015). Still other studies show no evidence of soil moisture-precipitation coupling in the Southern Great Plains region, based on in situ observation (Phillips and Klein, 2014), satellite (Taylor et al, 2012), and reanalysis data sets (Findell et al, 2011).…”
Section: Soil Moisture-precipitation Coupling In the Us Southern Greamentioning
confidence: 99%
“…Mesoscale studies are uniquely capable of documenting land-atmosphere interactions while simultaneously accounting for region-specific factors that could confound the results. For example, atmospheric stability in the Southern Great Plains region is significantly impacted by the strength and location of the Great Plains low-level jet (Higgins et al, 1997;Frye and Mote, 2010b). This is further complicated by the intrusion of squall lines and frontal systems during the warm season (Raddatz and Hanesiak, 2008), corresponding with conditions unfavorable for surface-induced convection (Matyas and Carelton, 2010 …”
Section: Soil Moisture-precipitation Coupling In the Us Southern Greamentioning
confidence: 99%
“…We utilize the methods of FRQ15, which were adopted from Frye and Mote (2010), to classify afternoon convective events into four categories based on synoptic and dynamic conditions. FRQ15 used this approach to identify convective precipitation events and exclude stratiform precipitation events.…”
Section: A Synoptic Environmentmentioning
confidence: 99%
“…They concluded that precipitation occurred preferentially over wet soils when atmospheric conditions were unfavorable for convection and the Great Plains low-level jet (LLJ) was not present. The synoptic-dynamic classification system that FRQ15 used was adopted from Frye and Mote (2010). It separates unorganized convective activity forced by surface flux/heating anomalies from more organized convection that initiated by mechanical lifting associated with the passage of fronts and low pressure systems.…”
Section: Introductionmentioning
confidence: 99%